Beers criteria and potentially inappropriate medications in elderly: awareness, practice, knowledge and barriers among community pharmacists in Nigeria (2022)
Background: Potential inappropriate medications (PIMs) used in the elderly are an avoidable source of disease and death. Beers Criteria is among the commonly used measures that document PIMs. Community pharmacists’ knowl edge on PIMs and existing criteria are essential to moderate the use of PIMs which would enhance overall health outcomes and costs. This study investigates awareness, knowledge, practice, and barriers of PIMs among community pharmacists in Ibadan, Nigeria. Methods: A cross-sectional study was carried out on 109 community pharmacists with the use of a self-administered questionnaire. Nine clinical vignettes based on the 2019 Beers Criteria were used to evaluate PIMs knowledge. Prac tice behavior regarding elderly clients was evaluated using a 5-point Likert scale with six items. Data were summa rized by descriptive and inferential statistics. Results: Respondents who knew guidelines that listed specifc PIMs were (49; 47.1%), and of these, (21; 42.9%) were aware of Beers Criteria. From all the respondents, only 45 (41.3%) demonstrated good knowledge of Beers Criteria, while 82 (75.2%) narrated good practice when dealing with elderly clients in terms of asking suitable questions and contemplating their ages while dispensing medications. Major barrier identifed was lack of knowledge of Beers Crite ria (80; 73.4%). Pharmacists who were aware of Beers Criteria statistically had better knowledge than others (p=0.003). Conclusion: Beers Criteria awareness among community pharmacists is sub-optimal in Ibadan, Nigeria. Although practice when dealing with elderly customers was satisfactory, the knowledge was unsatisfactory. This underscores the need to intensify the awareness and use of guidelines that document specifc PIMs such as Beers Criteria among community pharmacists.